The Binding of Benzoarylsulfonamide Ligands to Human Carbonic Anhydrase is Insensitive to Formal Fluorination of the Ligand1. Issue 30 (20th June 2013) - Lockett, Matthew R.; Lange, Heiko; Breiten, Benjamin; Heroux, Annie; Sherman, Woody; Rappoport, Dmitrij; Yau, Patricia O.; Snyder, Philip W.; Whitesides, George M.
<x xml:space="preserve">Abstract</x> It's the water that matters. Pairs of benzo‐ and perfluorobenzoarylsulfonamide ligands bind to human carbonic anhydrase with a conserved binding geometry, an enthalpy‐driven binding, and indistinguishable binding affinities (see picture). These data support the pervasive theory that the lock‐and‐key model disregards an important component of binding: the water, which fills the binding pocket of the protein and surrounds the ligand.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>